Il ritratto di Niceforo II Foca (963-969) nella Grande Piccionaia a Çavuşin. : La creazione di uno spazio sacro in Cappadocia alla metà del X secolo (Fenestella. Inside Medieval Art, 2024)
This article intends to highlight the historical significance and unique aspects of the pictorial cycle in the Great Pigeon House church at Çavuşin, Cappadocia. The church's paintings, commissioned by local leaders, celebrate the Byzantine army's victories over the Arabs and glorify Emperor Nicephorus II Phocas (963-969). Central to the decoration is a large portrait of Nicephorus and his imperial entourageplaced in the prothesis apse, aiming to sanctify the emperor and emphasize his role as God's representative on earth.The ‘image network’ on the northeast wall features unprecedented iconography depicting the triumph of John I Tzimisce and General Melias on horseback, followed by the Forty Martyrs of Sebaste. The relocation of the Baptism scene and parallels with figures like Constantine the Great present Nicephorus as a pious general and New Constantine, reflecting the duality of his personality. Overall, the pictorial cycle stands out as a distinctive artistic creation of 10th-century Byzantine art, set in a local context of military notables who emerge as creators of a sacred space, mediating between central power and provincial reality.
Keywords: Cappadocia; Imperial portrait; Cave church; Middle Byzantine art; Nikephoros II Phokas